The Presence of Description on Spirometry Disorder in the Old TB Patients who were Suffering from Dyspnea in BBKPM Surakarta - Muhammad Ali; Riana Sari; Sri Wahyu Basuki (Universitas Muhammadiyah Yogyakarta, 2019)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis signified by the formation of granuloma by the infected tissue. Old TB is a case of TB that once suffered from tuberculosis infection and declared as being cured. This research aims to know the presence of description on spirometry disorder in the old TB patients who were suffering from dyspnea in BBKPM Surakarta. Type of this research is descriptive research using Cross-Sectional approach. Population which becomes the subject of this research is the outpatient in the Non-TB Clinic of BBKPM Surakarta according to the criteria. Sampling was conducted using the method of Purposive Sampling and it was obtained 50 samples of old TB patients who were suffering from Dyspnea. Data were then processed by editing, coding, and tabulation. From the results of the data processing through editing, coding, and tabulation, there were 27 patients who were suffering from Obstruction disorder, 5 patients were suffering from Restriction disorder, 17 patients were suffering from mixed disorder (Obstruction and Restriction), and 2 patients were Normal. This research concluded who was suffering from dyspnea, in BBKPM Surakarta.